Business Data Analytic and Digital Marketing: Business Strategies in the Era of COVID-19 - Rehman Khan, Syed Abdul; Umar, Muhammad; Tanveer, Muhammad; Yu, Zhang; Janjua, Laeeq Razzak (2022 7th International Conference on Data Science and Machine Learning Applications (CDMA), 2022)
The Covid-19 pandemic has been assumed as a global pandemic as it caused disruption in all fields of life. The supply chain of manufacturing firms are also adversely affected by this pandemic. Keeping this in view, the current study is conducted to analyze the role of business data analytics (BDA) and digital marketing in improving Chinese firm performance during Covid-19. In this study, cross-sectional data was collected through questionnaire, and CB-SEM was employed to test hypotheses. The results indicate that BDA adoption helps firms move towards digital marketing and improve the firm's performance by effectively analyzing information, predicting behavioral model, and enhancing product delivery services. This article concluded that firms with well-developed technological infrastructure were least effected through Covid-19 pandemic. The current study recommends adopting BDA in firms as it helps firms respond to risky scenarios and enhances their resilience during uncertainty.